(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The objectives of research was (1) to examine and analyze the production and marketing of Gross Michel bananas which are currently in operation (2) to test the prototype production process and returns that have a suitable development to be discovered through the production units (farm example). Population in this study was 120 famers in district of Thayand and Banlad. A prototype of production and marketing bananas was surveyed and explored and then selected agriculturists a master 1experiment pilot. The area of 800 square meters was used with 100 of banana trees in testing. The total fixed cost consists of attractor rental (41.29%), land rental (23.73%, depreciation of equipment and banana root seed (14.23%) depreciation of equipment (08.85%) respectively, while the variable cost is high in labour (50.16%), fertilizer (28.46%), electricity bill (12.53%) and fuel of banana trees are used in the pilot. Then economic analysis of breakeven point was experimental to determine optimal production for farmers. The research found that the prototype of production was optimal Quantity at breakeven point Q= 469.80 kg. which is the best alternative, following Q = 502.24 kg. and Q =431.32 kg. respectively. The minimum alternative is 502.24 kg, and the best alternative is Q= 431.32 kg. The basic requirement of small farm is Q =469.80 kg. The results indicated that improving the soil condition, organic fertilizer, and the sale of products through the Agricultural Cooperative will be role model to get an excellent result